'Quantum effects' for classical light in modern waveguide circuits. (12th April 2019) - Bogatskaya, A V; Klenov, N V; Tereshonok, M V; Popov, A M
Abstract: Here we use approaches and concepts from quantum mechanics in order to analyze the propagation of classical electromagnetic waves in the elements of integrated optical circuits. These waveguide circuits are considered as potential wells between complex-shapes barriers formed by opaque media. This allowed us to construct in the framework of the slow-varying amplitude approximation for the wave equation an analogy between coherent oscillations in a quantum system and the redistribution in space of the field strength of a classical wave. We also demonstrated the methods to control the mode composition of a classical light in a spatially inhomogeneous waveguide structure. The proposed description was based on the analogy with Rabi-type oscillations in quantum mechanics.